2023
DOI: 10.1021/acs.est.3c05513
|View full text |Cite
|
Sign up to set email alerts
|

Bacterial Sulfate Reduction Facilitates Iodine Mobilization in the Deep Confined Aquifer of the North China Plain

Zhou Jiang,
Li Qian,
Mengjie Cui
et al.

Abstract: Bacterial sulfate reduction plays a crucial role in the mobilization of toxic substances in aquifers. However, the role of bacterial sulfate reduction on iodine mobilization in geogenic high-iodine groundwater systems has been unexplored. In this study, the enrichment of groundwater δ34SSO4 (15.56 to 69.31‰) and its significantly positive correlation with iodide and total iodine concentrations in deep groundwater samples of the North China Plain suggested that bacterial sulfate reduction participates in the mo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 9 publications
(1 citation statement)
references
References 59 publications
(132 reference statements)
0
1
0
Order By: Relevance
“…Laboratory studies on their sorption behavior have shown that IO 3 – has greater sorption than I – on iron-bearing minerals such as hydrous ferric oxide and goethite, as well as natural soils and sediments. Thus, the reduction of IO 3 – to I – could have an important influence on the mobility of iodine in natural systems. A previous study showed that the Fe­(II) solution was able to reduce IO 3 – , which was often cited to support that Fe­(III)-reducing bacteria residing in iodine-rich environments could facilitate iodine mobilization through abiotic IO 3 – reduction by biogenic Fe­(II). , However, the intermediates and stoichiometries of the abiotic reaction between Fe­(II) and IO 3 – have not been thoroughly investigated.…”
Section: Introductionmentioning
confidence: 99%
“…Laboratory studies on their sorption behavior have shown that IO 3 – has greater sorption than I – on iron-bearing minerals such as hydrous ferric oxide and goethite, as well as natural soils and sediments. Thus, the reduction of IO 3 – to I – could have an important influence on the mobility of iodine in natural systems. A previous study showed that the Fe­(II) solution was able to reduce IO 3 – , which was often cited to support that Fe­(III)-reducing bacteria residing in iodine-rich environments could facilitate iodine mobilization through abiotic IO 3 – reduction by biogenic Fe­(II). , However, the intermediates and stoichiometries of the abiotic reaction between Fe­(II) and IO 3 – have not been thoroughly investigated.…”
Section: Introductionmentioning
confidence: 99%